2018
DOI: 10.1515/revneuro-2017-0092
|View full text |Cite
|
Sign up to set email alerts
|

Gliotransmitters and cytokines in the control of blood-brain barrier permeability

Abstract: The contribution of astrocytes and microglia to the regulation of neuroplasticity or neurovascular unit (NVU) is based on the coordinated secretion of gliotransmitters and cytokines and the release and uptake of metabolites. Blood-brain barrier (BBB) integrity and angiogenesis are influenced by perivascular cells contacting with the abluminal side of brain microvessel endothelial cells (pericytes, astrocytes) or by immune cells existing (microglia) or invading the NVU (macrophages) under pathologic conditions.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 262 publications
0
34
0
1
Order By: Relevance
“…Activated astrocytes and microglial cells release neuroactive “gliotransmitters” via exocytosis, akin to neurotransmitter release from nerve endings ( 71 ), and alter neuronal chloride ( 72 ). They modulate blood–brain barrier permeability and BBB-mediated neuroinflammation and affect cell-to-cell communication ( 73 ). Gliotransmitters include GABA and taurine (inhibitory gliotransmitters) ( 72 ), as well as glutamate, d -serine, ATP, and l -lactate ( 71 ).…”
Section: Cks/cytokines and Their Receptorsmentioning
confidence: 99%
“…Activated astrocytes and microglial cells release neuroactive “gliotransmitters” via exocytosis, akin to neurotransmitter release from nerve endings ( 71 ), and alter neuronal chloride ( 72 ). They modulate blood–brain barrier permeability and BBB-mediated neuroinflammation and affect cell-to-cell communication ( 73 ). Gliotransmitters include GABA and taurine (inhibitory gliotransmitters) ( 72 ), as well as glutamate, d -serine, ATP, and l -lactate ( 71 ).…”
Section: Cks/cytokines and Their Receptorsmentioning
confidence: 99%
“…Recent scientific advances point toward the alterations in the inherent metabolic machinery of reactive glial cells as a result of the excessive demands of the overall brain tissue, as well as the individual cellular demands in disease state, resulting in altered neuron-glial interactions. The gliotransmitters (e.g., ATP, glutamate, and D-serine) released by glial cells impact the neuronglia communication (Osipova et al, 2018). It has been reported that impaired signaling between the microglia and neurons plays a significant role in the cognitive decline in AD, while the aberrant calcium and glutamate signaling in the reactive astrocytes also plays an important role in neuropathology (Teaktong et al, 2003;Lim et al, 2013).…”
Section: Altered Glial Metabolism In Neuron-glia Communication and Nementioning
confidence: 99%
“…Glutamate, an excitatory neurotransmitter essential for most brain activities, has been considered relevant to the pathogenesis of neuroinflammation, contributing to the development of several acute and chronic brain injuries [13]. The main process responsible for maintaining extracellular glutamate levels below toxic concentrations, thus favoring the physiological glutamatergic tonus, is the glutamate uptake activity of glutamate transporters located in neural cell membranes, mainly in astrocytes [14].…”
Section: Lecture Highlightsmentioning
confidence: 99%